Clinical appraisal of Lodhradi Kashaya on type 2 diabetes mellitus patients - Singh, Varun K.; Reddy, K. R. C. (International Journal of Clinical Trials, 2017)
Background: Lodhradi Kashaya (LKSD) is basically ayurvedic kwath dosage form, described as Madhumehajeet (winner of diabetes mellitus) in ayurvedic classics Basavarajeeyam and the same formulation in Vaidya Chintamani and Charaka Samhita too. The aim of this study was to assess prospectively the drug’s ability in management of type 2 diabetes. Methods: Total 31 patients were taken following the guideline mention in CCRAS protocol for diabetes mellitus research. They are divided into two groups, group A and B, given LKSD 4 g & 2 g TDS respectively for three-month follow up. They are investigated against their blood glucose, HbA1C and liver profile tests. Patients were also investigated for subjective parameters viz polyurea, polyphagia, exhaustion and constipation and their response has also been noted regarding palatability acceptance and ease of administration. Results: Patients has responded positively for formulation. Decrease in FBS and PPBS were found highly significant (P ˂ 0.001) in both groups but more in higher dose (group A). Decrease in HbA1C is also found highly significant in both groups. In LFT, SGOT level were also decreased more in group B in comparison to group A, and it is significant (P = 0.017 and 0.002). SGPT level were also decreased more in group B in comparison to group A, and it is significant in group B (P= 0.085 and 0.002). Conclusions: LKSD is having astringent taste due to tannins and phenols in it. It was found significant not only in controlling blood sugar but also in management of other factors related to diabetes mellitus.